Предмет: Алгебра,
автор: qasde12
((p-x+c)(p+x-c) как решить
Ответы
Автор ответа:
0
nafanya2014:
шестое по счету слагаемое +сх
Автор ответа:
1
По формуле
a²-b²=(a-b)(a+b)
(p-x+c)(p+x-c)=(p-(x-c))(p+(x-c))=p²-(x-c)²=p²-(x²-2xc+c²)=p²-x²+2xc-c²
a²-b²=(a-b)(a+b)
(p-x+c)(p+x-c)=(p-(x-c))(p+(x-c))=p²-(x-c)²=p²-(x²-2xc+c²)=p²-x²+2xc-c²
Похожие вопросы
Предмет: Английский язык,
автор: неллихорошист
Предмет: Немецкий язык,
автор: tetalexandr
Предмет: Русский язык,
автор: дильназСпецназ
Предмет: Русский язык,
автор: ali371